THE TECHNOLOGY OF METALWORKING IN MILLING MACHINES AND ITS TRAINING IN AN INNOVATIVE WAY (Scientific journal of the Fergana State University, 2022)
In addition to practical exercises on the use of milling machines, theoretical studies are the first. The use of computer technology and modern innovative technologies in our theoretical classes provides students with theoretical knowledge and understanding. Create interactive learning methods for machine tools to further expand knowledge. Familiarization of students with the methods of developing innovative pedagogical technologies.